Perceptions of environmental sustainability amongst mineworkers - F. Ince (Global Journal of Environmental Science and Management)
Environmental sustainability needs to use resources efficiently and effectively from macro to micro level with a systematic approach. The dualistic relationship between ecosystem and human beings require considering ecological and social systems as well as economic factors known as the three-legged approach. Individuals and their perceptions are also important in this approach because of the need of environmental awareness and behaviors. From this point of view, this study assesses the perceptions of local mine workers in the Göksu Valley about the environmental sustainability to understand the relationship between environmental, personal and organizational factors. Extroversion, conscientiousness, and agreeableness as the sub-dimensions of the personality have positive correlations with environmental sustainability. Also, working conditions and expert power of the leader have a significant relationship with environmental sustainability within the mine worker sample which has a high-level environmental sustainability mean. The perceptions of local workers or residents are important to gain specific information about areas which have a special ecosystem for agriculture and animals.